THE IMPACT OF THE TOURISM SECTOR ON THE ECONOMY OF BANTEN USING THE INPUT-OUTPUT MODEL - Endang Puji Astutik; Lukytawati Anggraeni; Bambang Djuanda; Wiwiek Rindayati (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze the role and impact of the tourism sector on the Banten economy. The analytical method used is the 2016 Banten Province Input-Output analysis, for the classification of 52 industrial sectors and 17 business fields. The approach used,; analyzing backward and forward linkages which are key and superior sectors in the Banten economy, multipliers (output, income and employment), describing the priority scale for developing tourism sectors in Banten, describing shock analysis of government policy, if there is an increase in the tourism budget and its impact on Banten economy. The results of the study show that the backward and forward linkage analysis of all tourism-related sectors is very strong with IKBL (backward linkage index) and IKDN (forward linkage index) values ​​above 1, the highest forward linkage value is 2.6 in the air transport sector. The highest value of backward linkage is 1.55 in the rail transport sector. Business fields related to the tourism sector in Banten are a key and superior sector in the Banten economy, as is the electricity sector. The highest value of the multiplier lies in income, namely; information and communication sector with a value of 5.06. The next highest multiplier value lies in the output and labor multiplier in the transportation sector. If an additional budget is given, the highest multiplier value (output, income and employment) lies in the accommodation and food and drink provision sector. So, the most appropriate policy is, if government spending and private investment, focus on opening new businesses in sectors related to tourism through prioritizing the provision of accommodation and food and drink, transportation (air transportation, rail transportation, warehousing and supporting services). transportation, postal and courier, land transportation, sea transportation, river, lake and ferry transportation), information and communication sector, corporate services and other services.